2013
DOI: 10.1093/abbs/gmt085
|View full text |Cite
|
Sign up to set email alerts
|

Jagged-1/Notch3 signaling transduction pathway is involved in apelin-13-induced vascular smooth muscle cells proliferation

Abstract: The apelin/apelin receptor (APJ, apelin-angiotensin receptor-like 1) system is a newly deorphanized G protein-coupled receptor system. Both apelin and APJ that are important regulatory factors are expressed in the cardiovascular system. Our previous studies demonstrated that apelin-13 significantly stimulated vascular smooth muscle cell (VSMC) proliferation. In this paper, our data suggested that the Jagged-1/Notch3 signaling transduction pathway is involved in apelin-13-induced VSMC proliferation by promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 21 publications
3
49
0
Order By: Relevance
“…Nakamura et al [63] found that ERS promoted proliferation and migration of human retinal microvascular endothelial cells by increasing the expression of Bip at both the mRNA and protein levels and enhancing the formation of a Bip/T-cadherin immunocomplex. In an oxygen-induced retinopathy (OIR) model in mice, Bip was observed in the retinal microvascular endothelial cells; this finding has many similarities to observations of the endogenous ligand of APJ receptor apelin-13 [64][65][66] . Yang et al [67] reported that hypoxia, especially intermittent hypoxia, induced endothelial cell apoptosis, possibly through ERS.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiosupporting
confidence: 57%
See 1 more Smart Citation
“…Nakamura et al [63] found that ERS promoted proliferation and migration of human retinal microvascular endothelial cells by increasing the expression of Bip at both the mRNA and protein levels and enhancing the formation of a Bip/T-cadherin immunocomplex. In an oxygen-induced retinopathy (OIR) model in mice, Bip was observed in the retinal microvascular endothelial cells; this finding has many similarities to observations of the endogenous ligand of APJ receptor apelin-13 [64][65][66] . Yang et al [67] reported that hypoxia, especially intermittent hypoxia, induced endothelial cell apoptosis, possibly through ERS.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiosupporting
confidence: 57%
“…Apelin-13/APJ system has been identified as a potential therapeutic target for hypertension [166] and atherosclerosis [167] . Our laboratory has demonstrated that apelin-13 induced proliferation of vascular smooth muscle cells [66,168] and rat bone marrow-derived mesenchymal stem cells [169] through the Jagged-1/Notch3, cyclin D1 and AKT/ GSK3β/cyclin D1 pathways. However, other researchers demonstrated that apelin-13 is no longer merely a potential therapeutic target; it may serve as a new peptide to treat I/R injury.…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%
“…Apelin is a novel angiogenic factor in human non-small cell lung cancer (NSCLC) [18]. Our recent studies demonstrated that apelin-13-induced adhesion of monocytes to human umbilical vein endothelial cells via PI3K/14-3-3 [19] and apelin-13 also promoted vascular smooth muscle cell (VSMC) proliferation through PI3K-Akt-ERK1/2-cyclin D1 pathway [20] and Jagged-1/Notch3 signaling pathway [21]. We also confirmed that apelin-13 stimulates VSMC proliferation by promoting the G1/S phase transition, and this effect is mediated in part by an apelin-pERK1/ 2-cyclin D1 signal cascade [22].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of ERK was decreased, indicating that NOX4, as the upstream signaling molecule of ERK, is involved in the promoting effects of apelin-13 on the proliferation of VSMCs. In another study, Li et al (31) also found that apelin-13 promoted the proliferation of VMSCs by activating the ERK-Jagged-1/Notch3-cyclin D1 pathway. Li et al found that apelin-13 promoted the expression of NOX4 and the increased generation of ROS in VSMCs (19), and Lu et al found that apelin-APJ induced ICAM-1, VCAM-1 and MCP-1 expression through the NF-κB/JNK signaling pathway (26).…”
Section: Apelin Induces Atherosclerosis By Promoting Oxidative Stressmentioning
confidence: 90%